Effect of menstrual cycle phase and hormonal contraceptives on resting metabolic rate and body composition - Kuikman, M. A.; McKay, A. K. A.; Minahan, C.; Harris, R.; Elliott-Sale, K. J.; Stellingwerff, T.; Smith, E. S.; McCormick, R.; Tee, N.; Skinner, J.; Ackerman, K. E.; Burke, L. M. (International Journal of Sport Nutrition and Exercise Metabolism, 2024)
The cyclical changes in sex hormones across the menstrual cycle (MC) are associated with various biological changes that may alter resting metabolic rate (RMR) and body composition estimates. Hormonal contraceptive (HC) use must also be considered given their impact on endogenous sex hormone concentrations and synchronous exogenous profiles. The purpose of this study was to determine if RMR and dual-energy X-ray absorptiometry body composition estimates change across the MC and differ compared with HC users. This was accomplished during a 5-week training camp involving naturally cycling athletes (n = 11) and HC users (n = 7 subdermal progestin implant, n = 4 combined monophasic oral contraceptive pill, n = 1 injection) from the National Rugby League Indigenous Women`s Academy. MC phase was retrospectively confirmed via serum estradiol and progesterone concentrations and a positive ovulation test. HC users had serum estradiol and progesterone concentrations assessed at the time point of testing. Results were analyzed using general linear mixed model. There was no effect of MC phase on absolute RMR (p = .877), relative RMR (p = .957), or dual-energy X-ray absorptiometry body composition estimates (p > .05). There was no effect of HC use on absolute RMR (p = .069), relative RMR (p = .679), or fat mass estimates (p = .766), but HC users had a greater fat-free mass and lean body mass than naturally cycling athletes (p = .028). Our findings suggest that RMR and dual-energy X-ray absorptiometry body composition estimates do not significantly differ due to changes in sex hormones in a group of athletes, and measurements can be compared between MC phases or with HC usage without variations in sex hormones causing additional noise.